Indonesia - Fulgensius Efrem Men; Kanisius Mandur; Yohannes Marriono Jamun; Silverster T. R. Bagio (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This study aims to analyze the mathematical resilience of preservice teachers in posing mathematical problems based on their mathematical literacy ability. This research employed a descriptive qualitative approach, involving students of a mathematics education study program as the research subjects. The research instruments included a mathematical literacy test, a mathematical problem-posing task, a mathematical resilience questionnaire, and semi-structured interviews. The data were analyzed through data reduction, data presentation, categorization of findings, and conclusion drawing. The results indicate that preservice teachers with high mathematical literacy tend to demonstrate strong mathematical resilience, as reflected in their perseverance, self-confidence, strategic flexibility, and willingness to revise the problems they pose. In contrast, preservice teachers with low mathematical literacy tend to produce routine, less contextual problems and have trouble maintaining their strategies when facing obstacles. These findings affirm that mathematical resilience and mathematical literacy are two mutually supportive aspects in producing creative, contextual, and meaningful mathematical problem posing. The implications of this study point to the need to strengthen problem-posing-based learning in mathematics teacher education. Penelitian ini bertujuan untuk menganalisis resiliensi matematis calon guru dalam pengajuan soal matematika berdasarkan kemampuan literasi matematika. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek mahasiswa program studi pendidikan matematika. Instrumen penelitian meliputi tes literasi matematika, tugas pengajuan soal (problem posing), angket resiliensi matematis, dan wawancara semi-terstruktur. Data dianalisis melalui reduksi data, penyajian data, kategorisasi temuan, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa calon guru dengan literasi matematika tinggi cenderung memiliki resiliensi matematis yang kuat, ditandai dengan ketekunan, kepercayaan diri, fleksibilitas strategi, dan kemauan merevisi soal. Sebaliknya, calon guru dengan literasi matematika rendah cenderung menghasilkan soal rutin, kurang kontekstual, dan mengalami kesulitan mempertahankan strategi ketika menghadapi hambatan. Temuan ini menegaskan bahwa resiliensi matematis dan literasi matematika merupakan dua aspek yang saling mendukung dalam menghasilkan pengajuan soal matematika yang kreatif, kontekstual, dan bermakna. Implikasi penelitian ini mengarah pada perlunya penguatan pembelajaran berbasis problem posing dalam pendidikan calon guru matematika.